التورق المصرفي آخر انحرافات المصارف الإسلامية: دراسة تحليلية للأنشطة لبنك إسلام ماليزيا 1988-2016 - السبوسي، سعيد سيف Alsabousi, Said Saif (جامعة الشهيد حمه لخضر الوادي - كلية العلوم الاقتصادية والتجارية وعلوم التسيير, 2019)
حاولنا من خلال هذه المقال تسليط الضوء على بعض الانحرافات التي وقعت فيها المصارف الإسلامية عند القيام بنشاطاتها التمويلية، والتي أخرجتها عن السكة التي رسمتها الشرعية الإسلامية لها من خلال فقه المعاملات المالية الإسلامية، ودعا إليها أوائل المنظرين لفكرة الصيرفة الإسلامية، وتتمثل الانحرافات التي تناولناها بالدراسة تهميش صيغ المشاركات، التركيز الاستثماري، والاعتماد على الصيغ المحرمة والمشبوهة فعرفنا طبيعة هذه الانحرافات وأسبابها ودرجة خطورتها وكيفية تصحيح هذه الانحرافات مع الإسقاط في كل ذلك على الأنشطة التمويلية لمصرف إسلام ماليزيا وبالتركيز على خطورة الانحراف الثالث المتمثل في الاعتماد على الصيغ المشبوهة والمحرمة والتي يعتبر التورق المصرفي أهمها.
In this article, we tried to shed light on some of the deviations that occurred in the Islamic banks in carrying out their financing activities, which they took out of the line drawn by the Islamic legitimacy through the jurisprudence of Islamic financial transactions and called by the early theorists of the idea of Islamic banking. The marginalization of the forms of participation, investment focus, and reliance on the forbidden and suspicious formulas, we knew the nature of these deviations and their causes and degree of seriousness and how to correct these deviations with the projection in all this on the financing activities of the Bank of Islam Malaysia and Focus on the seriousness of the third deviation of the reliance on suspicious and forbidden formulas, which is considered the most important banking Tawar.
Keywords: ماليزيا -- البنوك الإسلامية -- التورق -- التمويل الإسلامي -- بنك إسلام ماليزيا